On the question of the language behavior of Kyivans in sociolinguistic dimensions - Makarets, Iuliia (Current issues of Ukrainian linguistics: theory and practice, 2020)
The article presents the results of a survey conducted within the project under the grant of the President of Ukraine F82 "Linguo-sociological monitoring of the dynamics of the structure and status of the Ukrainian language in modern times" (2019). The study involved 400 Kyivans 18 to 65 years old. The main goal was to supplement the sociolinguistic studies of the language situation of Ukraine of recent years with new data, but not to duplicate them. Till now, researchers focus on the language of everyday communication of respondents, on the native language of their parents, on the language of communication in the family, with friends and in professional life. Therefore, 10 questions were selected for the questionnaire, which should reveal the status perception of language and language guidelines of the respondents. The obtained data show, that the native language self-determination of Kyivans not always determines their language behavior. 73.25% of respondents called Ukrainian their native language, but the informational and cultural space in which they live remains mostly bilingual or Russian-language. 79.75% of respondents said, that the state should support functioning of the Ukrainian language, which should indicate a fairly high value attitude to the language. However, 32% consider the measures, that were taken by the state to ensure the functioning of the Ukrainian language, for example, in media, which so far were predominantly Russian- language, needless and 22% say, that the quota did not affect the situation in any way. More than 32% of Ukrainians six months after the adoption of the new version of the spelling standard did not acquaint with it or even did not hear about it at all, which indicates indifference to language development. There is significant percentage of those, who do not see value in the national language and are not aware of the need for public language policy aimed at supporting it. This indicates an insufficient level of language consciousness of Ukrainians. Reflections on the Ukrainian language are mostly caused by the fact, that it is a frequent subject of political debate, rather than by awareness of its essence as a cultural and nation-building factor. Therefore, there is an urgent need to shift the emphasis in its perception from its purely political role to cultural and value essence.